THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND CORPORATE FINANCIAL PERFORMANCE – EVIDENCE FROM EMPIRICAL STUDIES - Janevski, Zoran; Davitkovska, Elena; Majovski, Irina; Petkovski, Vladimir (My University, 2017)
This research suggests that companies that aim for good corporate governance also have better financial performance. Previous research in this area has not lead to a broader consensus of this assertion, in terms of the intensity of this relationship and also according to its direction. This research is based on analysis of 50 empirical studies conducted in 13,769 companies worldwide, in which the existence and nature of the relationships between the various characteristics of corporate governance are analyzed, on the one hand, and various variables of corporate financial performances, on the other hand. The results of the research confirm that there is a positive relationship between corporate governance and corporate financial performances.
Keywords: Corporate Governance; Corporate Performance; Financial Performance